INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI KEGIATAN EKTRAKURIKULER DI SMP RAUDATUT THOLABAH JENGGAWAH JEMBER: Learning Innovation of Islamic education through extracurricular activities at Raudatut Tholabah Junior High School Jenggawah Jember - Mursalim Mursalim; Hatta Hatta (Fenomena, 2019)
Innovation is a necessity because there is no sedentary life. Times keep changing, and only people or institutions continue to innovate to survive. While institutions with no innovation are slow or fast, they are abandoned, stale, not marketable, and do not keep up with the times. The innovation of pesantren-based schools is an effort to ensure that an institution continues to withstand the onslaught of the modern era. Above destructive reality, if not responded to quickly, precisely, and intelligently will have a more severe impact. In an educational context, innovative ideas about pesantren-based schools and PAI learning innovation are one of the solutions which must be taken. Generally, PAI is terminology in schools, but it is not in Junior High School of Raudatut Tholabah; PAI learning developed at the school are Al-Qur'an - Hadith, Fiqh, SKI, and Aqidah Akhlak. The innovation of Islamic Learning Education Through Extracurricular Activities in SMP Raudatut Tholabah Jenggawah of Jember. It is the strengthening of religious values through the activities of having Dhuha Prayer and Dhuhur together, Reading and writing, tahfidzul and reading Al Qur'an together, Academic Guidance and Counseling Services, Scouting, Sports, and the arts.